The influence of different winter nutritional planes, particularly submaintenance level, on the subsequent growth, development, efficiency of feed utilization and carcass quality of young beef steers - Verbeek, Willem Albert (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1958.